2011
DOI: 10.1159/000329628
|View full text |Cite
|
Sign up to set email alerts
|

CSF Shunt Complications in Infants – An Experience from Pakistan

Abstract: Aims and Objective: The main aim of the study was to find out the postoperative complications and long-term outcome of cerebrospinal fluid-shunted patients in an infantile age group with a poor socioeconomic background. Material and Methods: A prospective study of 100 cases of infantile hydrocephalus was conducted at Pakistan Institute of Medical Sciences, Islamabad, Pakistan. All selected patients suffering from congenital and post-meningitic hydrocephalus were operated on for ventriculoperitoneal shunt. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Other reported causes of late presentation include social taboos, low socioeconomic status, ignorance, and misunderstanding of the early symptoms of hydrocephalus. [ 5 7 8 9 ] Shunt-related complications and poor outcomes are more common in patients with delayed shunt insertion, and this is a common occurrence in developing countries. The risk factors for these include co-morbidities like anemia and malnutrition, advanced presentation, and lack/delay of adequate diagnostic imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other reported causes of late presentation include social taboos, low socioeconomic status, ignorance, and misunderstanding of the early symptoms of hydrocephalus. [ 5 7 8 9 ] Shunt-related complications and poor outcomes are more common in patients with delayed shunt insertion, and this is a common occurrence in developing countries. The risk factors for these include co-morbidities like anemia and malnutrition, advanced presentation, and lack/delay of adequate diagnostic imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Late presentation has also been attributed to social taboos and socioeconomic conditions. [ 5 6 ] Better outcomes have been reported in patients who were shunted earlier than those who underwent late shunt surgery. [ 7 8 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…50% of patients with congenital hydrocephalus had associated congenital anomalies. Common post-operative complications included shunt obstruction (24%), infection (20%) intracerebral hemorrhage (0.5%) and subdural hematoma (0.5%) 27 . Such postoperative complications are more common in low-socioeconomic settings like Pakistan.…”
Section: Hydrocephalusmentioning
confidence: 99%
“…However, the situation is not the same in less developed countries like Pakistan. Bakhsh reported that infants who developed complications due to CSF shunting often presented very late to the healthcare facilities due to socioeconomic conditions and ignorance [5]. The author further highlighted that up to 40% of deaths occurred in infants who had congenital hydrocephalus.…”
Section: Introductionmentioning
confidence: 97%